THEORETICAL ASPECTS OF THE STUDY OF LEXICAL UNITS "TAUTOLOGY" AND "PLEONASM" IN MODERN RUSSIAN - Kakharova Nilufar Nuridinovna (Web of Journals Publishing, 2025)
This article discusses theoretical approaches to the study of lexical units "tautology" and "pleonasm" in modern Russian. Their nature, functions in the text and the relationship between them are analyzed. Special attention is paid to the difference between conscious and unconscious use of these phenomena, their stylistic and communicative functions. The issues of lexical redundancy and its perception in the modern linguistic consciousness are also touched upon.
Keywords: tautology, pleonasm, vocabulary, speech redundancy, stylistics, repetition, linguistic consciousness.